The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1435-5597.1997.tb00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary, Return and Onward Migration in the U.S. And Canada: Is There a Difference?

Abstract: Using microdata sources available from the U.S. Census Bureau and Statistics Canada, this paper contrasts primary, return and onward migration in the two countries. These classifications are based on information on the region (state or province) of birth and region of residence at the start and end of the census period. To study the propensities to make a primary, return or onward migration, rates are calculated according to Long (1988) and compared with previous census periods. Analysis reveals that both coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 0 publications
1
20
0
3
Order By: Relevance
“…However, whatever the reason for this phenomenon, such reduced initial mobility may well have long-term implications for these non-White graduates, in that their subsequent migration propensities and consequently their long-term incomes will be reduced relative to those who were more mobile at the earlier stage. This implication is based on conclusions from a large body of research, which links the lifetime earnings of the population in general to the nature of sequential migration behaviour (DaVanzo 1976(DaVanzo , 1983Newbold 1997). Lower initial migration propensities are highly correlated with lower subsequent migration propensities, and both are correlated with lower overall lifetime earnings.…”
Section: Discussionmentioning
confidence: 99%
“…However, whatever the reason for this phenomenon, such reduced initial mobility may well have long-term implications for these non-White graduates, in that their subsequent migration propensities and consequently their long-term incomes will be reduced relative to those who were more mobile at the earlier stage. This implication is based on conclusions from a large body of research, which links the lifetime earnings of the population in general to the nature of sequential migration behaviour (DaVanzo 1976(DaVanzo , 1983Newbold 1997). Lower initial migration propensities are highly correlated with lower subsequent migration propensities, and both are correlated with lower overall lifetime earnings.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that people tend to return to places where they lived before (DaVanzo, 1981;DaVanzo and Morrison, 1981;Fischer and Malmberg, 2001;Morrison and DaVanzo, 1986;Newbold, 1997Newbold, , 2001; for the Netherlands: Harts and Hingstman, 1986;Nicolaas and Sprangers, 2000). Return moves are made for several reasons: because of ties to the place of origin (that is, the social space and activity space); as a corrective move (out of regret about having moved away; see Morrison and DaVanzo, 1986;Newbold, 1996); or emotional attachment to a place (Rubinstein and Parmelee, 1992;Feldman, 1996).…”
Section: Residential Experiencementioning
confidence: 99%
“…By the same token, of 4800 partners (of the principal worker) only 325 were men. TURNBULL (1992) or HOTCHKISS andWHITE (1993 It has been empirically observed in the U.S. that repeat migration is an important issue in migration studies: a small proportion of workers show a higher than average migration propensity (they migrate many times during their working life), while the migration propensity of most workers is well below average (DIERX, 1988;EVANS, 1990;BORJAS et al, 1992;GRUBER and ZEAGER, 1994;NEWBOLD, 1997). Some authors divide workers into "movers" and "stayers" according to their migration propensity.…”
Section: -Commuting and Residence Changes In Catalonia 1986-1996: mentioning
confidence: 99%